Improvement of the control system over drum boilers for burning combustible artificial gases - Maksymov, Maksym; Lozhechnikov, Vadim; Maksymova, Oksana; Lysiuk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2017)
One of the promising directions in the development of power industry in Ukraine is the implementation of low-cost activities with a fast payback period, which would make it possible, without attracting significant funds, and in the shortest possible time, to bring down fuel and electricity consumption. Such activities could include the use of the new structural circuits of automated control at the existing steam generators running on organic fuel, which will allow, without a substantial equipment modernization, the use of combustible artificial gases as fuel. A limiting factor for the combustion of artificial gases in energy drum boilers is their low calorific value and insufficient throughput of the regulating valve, which depends on density of the regulated medium. We examined a possibility of burning artificial gases in energy boilers without considerable modernization of basic equipment (replacement of burners and controlling elements, installation of additional steam generating equipment) both for a single drum boiler and a group of boilers operating in the common steam line. In both cases, in order to increase the throughput, a gas compressor is employed. It was established that for the aligned work of the compressor with a heat load ACS of one boiler, it is necessary to define a transfer function of the communication device. To control a group of boilers, we synthesized multidimensional optimal ACS that would make it possible to improve the integrated quality indicators to regulate pressure and consumption of superheated steam. The implementation of the obtained technical solutions will improve energy security and effectiveness of the industrial potential of Ukraine.